High altitude pulmonary edema in a native highlander: A case report from Nepal - Ishwor Thapaliya; Adesh Kantha; Krishna Datta Bhatta; Aakash Deo; Dilip Sharma Banjade; Sushil Kumar Yadav (International Journal of Medical Students)
BACKGROUND: High altitude pulmonary edema (HAPE) is a non-cardiogenic pulmonary edema, that usually occurs in unacclimatized lowlanders rapidly ascending above 2,500-3,000 m and in highlanders returning from lower altitudes, with both forms likely sharing the same pathophysiology. Its incidence among Himalayan trekkers and Alp’s climbers is approximately 4%, often  varying with rate of ascent. It usually manifests within 2–4 days of arriving at altitudes exceeding 2,500 meters. The factors predisposing HAPE include prior respiratory infection, rapid ascent, prior history of HAPE, genetic predisposition. Patients with HAPE exhibit increased pulmonary artery pressures, normal left atrial pressure, heightened pulmonary vasoreactivity to hypoxia, and often benefit from treatments lowering pulmonary artery pressures.